Preparation and characterization of plasticized starch/halloysite porous nanocomposites possibly suitable for biomedical applications. Issue 4 (20th August 2014) - Schmitt, Helene; Creton, Nicolas; Prashantha, Kalappa; Soulestin, Jeremie; Lacrampe, Marie‐France; Krawczak, Patricia
ABSTRACT Novel porous bionanocomposites based on halloysite nanotubes as nanofillers and plasticized starch as polymeric matrix were successfully prepared by melt‐extrusion. Foaming was obtained by adding water as natural blowing agent, and by increasing the die temperature. Both the expansion ratio and the porosity increase with increasing die temperature. Addition of high water content allows reducing the foaming temperature. Moreover, the introduction of halloysite has double benefits: these fillers act both as a nucleating agent increasing the porosity and as a barrier agent increasing the proportion of small cells. Foams based on plasticized starch with a blend of glycerol and sorbitol loaded with 6 wt % of halloysite, extruded at 117°C, present the cellular structure and the mechanical properties required for scaffold applications. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41341.